An analysis on the need of developing GEMAS literacy journals using the STAD Model for writing reviews in junior high schools - Hipana, Wiwin; Mulyati, Yeti; Nugroho, Rudi Adi; Cahyani, Isah; Kurniawan, Khaerudin (Universitas Muhammadiyah Malang, 2026)
This study is initiated due to the limited review-writing proficiency demonstrated by junior high school students, which remains inconsistent with the critical and evaluative thinking competencies emphasized in Indonesian language learning. This issue is associated with the predominance of less collaborative instructional approaches and the lack of systematic literacy media capable of guiding students in the processes of reflection, idea organization, and critical expression. This study aims to analyze the needs of teachers and students for the development of the GEMAS Literacy Journal based on the Student Teams Achievement Division (STAD) model in learning to write reviews in junior high schools. The study used a qualitative descriptive approach in the needs analysis stage as the initial part of the model development. Data were obtained through interviews with three Indonesian language teachers, questionnaires of 37 eighth-grade students, and observation and documentation of learning. Data were analyzed through systematic reduction, presentation, and drawing conclusions. The results of the study indicate a gap between the demands of writing review competencies and ongoing learning practices, so teachers and students need media that can integrate group collaboration and literacy reflection in a structured manner. The development of the GEMAS Literacy Journal based on STAD is considered relevant to bridge this need because it is able to combine individual responsibility, teamwork, and reflective guidance in the writing process. Thus, this study confirms the urgency of developing collaborative literacy media as a basis for innovation in learning to write reviews in junior high schools.